Gambaran Pengetahuan dan Sikap Ibu dalam Memenuhi Asupan Kebutuhan Gizi Balita Dengan Stunting di Wilayah Kerja Puskesmas Singaparna Kabupaten Tasikmalaya - Sri Wahyuni; Evi Irmayanti; Wawan Rismawan (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Stunting cases can be defined as a condition of failure to thrive in children. Data obtained from the Tasikmalaya Regency office, the stunting rate in 2019 reached 4,887 people and the Singaparna Health Center was included in the stunting red zone. This study aims to determine the knowledge and attitudes of mothers in meeting the nutritional needs of toddlers with stunting. The research method used in this research is descriptive quantitative. The population is all mothers who have children under five, 2,495 people, a sample of 345 people, random sampling technique, research time 23 April - 23 May 2021, Place at Singaparna Health Center, Tasikmalaya Regency. The procedure for collecting primary data and secondary data. Data collection techniques that can be done are through questionnaires (Questionnaire), the questionnaire method is a google form data collection method. The results of this study indicate that the description of the knowledge and attitudes of mothers regarding the intake of nutritional needs of toddlers with stunting in the work area of ??the Singaparna Public Health Center, Tasikmalaya Regency, namely the results obtained from the level of good knowledge of 60 people (66.7%), sufficient knowledge of 23 people (25.6% ), lack of knowledge as many as 7 people (7.8%) and the results obtained a good attitude level as many as 73 people (81.1%), sufficient attitude as many as 17 people (18.9%), lack of attitude does not exist (0%). The conclusion after this research is that researchers can find out the description of knowledge and attitudes of mothers in meeting the nutritional needs of toddlers with stunting in the work area of ??the Singaparna Health Center, Tasikmalaya Regency, namely mother's knowledge about nutritional intake of toddlers with stunting mostly have a good level of knowledge and about mother's attitude about intake the nutritional needs of toddlers with stunting mostly have a good attitude level.